Prevalence of depression and its associated factors among undergraduate admission candidates in Bangladesh: A nation-wide cross-sectional study. - Md Abu Bakkar Siddik; Md Nafiul Hasan; Al Mahmud; Morioum Sarkar Munmun; Mahmudul Hasan Milad; Akher Ali; Zobayer Ahmed; Md Jamal Uddin (PLoS ONE, 2023)
Background The undergraduate admission test is one of the most stressful assessments in a student's life, as it is required for admission to any of Bangladesh's public universities or medical colleges. Those taking the admissions test are under a lot of pressure to perform well. This study aimed to determine the prevalence of clinical depression among Bangladeshi admission candidates and the factors that contribute to it. Methodology Patient Health Questionnaire (PHQ-9) and other socio-demographic information were collected from 5263 students from all over Bangladesh. Apart from descriptive statistics and chi-square tests, an ordinal logistic regression model was also applied to determine the factors associated with depression. Results The study revealed that among the undergraduate admission applicants, 74% of individuals were affected by depression, while 26% experienced moderate depression, 26% experienced moderately severe depression, and 22% experienced severe depression. The level of depression among females was 1.8 times higher than the male admission candidates. Our analyses found that gender (p <0.001), exercise (p <0.001), pre-marital relationships (p <0.001), daily study time less than 3 hours (p <0.001), practice of religion (p <0.001), victim of blackmail (p <0.001), family unrest (p <0.001), major illness (p <0.001), COVID-19 infection (p <0.001), GPA in higher secondary (p <0.001), mental problem (p <0.001), all categories of the variable confidence level for exam preparation (p <0.001) had a significant impact on increasing depression. Conclusion The research found a severe rate of depression among Bangladeshi undergraduate admission candidates. Interactive mental health care programs must include family and teachers to tackle the problem. To alleviate mental stress and depression, students should learn to nurture their mental health.